HUKUM-HUKUM EPOS AXEL OLRIX DALAM STRUKTUR DONGENG ORMU, PAPUA - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
Ormu’s folktale is the folktales that life and grown on Ormu etnic in Kabupaten Jayapura, Papua Province. Some of reseach about Ormu’s folktale had done, but not for research about its structure based on Axel Olrix’s epic law. It becomes the background of this research. This research tells about epic law of Axel Olrix on structure of folktales in Ormu, Papuan. The goals of this research is to analyze and to desribe about Axel Olrix’s epic law that applied on its structure. Methods of this research is qualitative. Data was collected by documentation technique by library research. It was analyzed by composing the plot of folktale then to describe it, so the characters can be known. For the last, the structure of that folktale was found their compatibility on Axel Olrix’s epic law. The result of this research was found that all Ormu’s folktales has forward plot with limited character, their were bundled by two equal of epic law. Each folktale bundles by different epic law, its totally between two untill eight epic law.